Perancangan Sistem Pencatatan dan Laporan Keuangan Berbasis Web pada CV Chalista Engineering Batam - Syaeful Anas Aklani; Daniel Lim (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
CV Chalista Engineering Batam is a business producing tools to hold goods or hardware in the production process located at Ruko Tembesi Point, Batu Aji District, Batam. This company has a problem with paper-based financial records and manual reporting using excel. So the company needs a system that can record and generate reports. The method used in the design and development is the System Development Life Cycle (SDLC) method by conducting needs analysis, design, development, testing, and implementation. The results of this study are a web-based financial reporting and recording system for CV Chalista Engineering Batam. With this system, the financial recording process will be easier, more effective and minimize the occurrence of data errors.